Psychological Aspects in Emergency Situations - Gazisovna, Galimova Liliya (European Journal of Life Safety and Stability (2660-9630), 2023)
This article discusses the psychological aspects (heartache, anger, anger, guilt, fear, anxiety, inappropriate behavior) in emergency situations.